The concept of time in children aged 5 to 10 (Journal of Parents and Teachers, 2026)
Through personal experiences, visual representations and conventional language, this article examines how children develop a sense of time and proposes teaching strategies to facilitate their learning in a natural way. To this end, the educational use of three key tools will be necessary: the clock, the calendar and timelines.
Keywords: Concept of time; experiences; icons